(5′R)-and (5′S)-purine 5′, 8-cyclo-2′-deoxyribonucleosides: reality or artifactual measurements? A reply to Chatgilialoglu's comments (this issue). (3rd October 2019) - Cadet, Jean; Di Mascio, Paolo; Wagner, J. Richard
Abstract: This rebuttal letter is aimed at refuting the poor and false arguments elaborated by Chatgilialoglu (preceding article) in his response to the position article (Cadet et al. Free Radic Res 2019;53:574–577) that focussed on the putative reliability of the HPLC-MS/MS measurements of five radiation-induced damage to cellular DNA, which included 8-oxo-7, 8-dihydro-2'-deoxyadenosine and the (5′ R ) and (5′ S ) diastereomers of 5′, 8-cyclo-2′-deoxyadenosine and 5′, 8-cyclo-2′-deoxyadenosine (Krokidis et al. Free Radic Res 2017;51:470–482). Unfortunately, none of the main issues we raised on the suitability of the analytical approach and the shortcomings associated with DNA extraction in HPLC based measurement methods of oxidatively generated damage in cells were properly considered in Chatigilialolu's letter. The main questionable issues include the lack of information on the sensitivity of HPLC-MS/MS analysis, the absence of a dose curve that is essential in the formation of damage and the nonconsideration of artifactual oxidation.